Treatment of pulmonary aspergilloma in cystic fibrosis by percutaneous instillation of amphotericin B via indwelling catheter. Issue 7 (July 1995) - Ryan, P J; Stableforth, D E; Reynolds, J; Muhdi, K M
Abstract : Pulmonary aspergilloma is a rare complication of cystic fibrosis and is a contraindication to transplantation. The elimination of an aspergilloma in a 24 year old patient with cystic fibrosis by percutaneous instillation of amphotericin B is described, enabling her to be accepted on a lung transplantation programme.